Rasionalitas Politik Generasi Milenial terhadap Kandidat Mantan Narapidana Korupsi di Pemilu DPD RI Sulawesi Tenggara - Madani, Saptarina Imelda (Indonesian Democracy Research Center, 2024)
This study aims to analyze the rational choices of the millennial generation regarding the nomination of former corruption convicts in the Southeast Sulawesi electoral district for the Regional Representative Council (DPD RI) in the 2019–2024 period. Using a qualitative-descriptive approach, the research involved eight Political Science students from Halu Oleo University who were aware of the nomination of former corruption convicts. The findings reveal that millennials tend to reject problematic candidates based on experience value, reflecting disappointment with past corruption cases. However, some respondents were still willing to support such candidates if they demonstrated clear vision, mission, and satisfactory political performance (decision value). These results indicate that millennial political behavior is not strictly dichotomous but shaped by the interplay of past experiences and rational calculations of future political benefits.